Alauda arvensis subsp. herberti Hartert ... - LeCROY, M. A. R. Y. (Zenodo, 2003)
Alauda arvensis herberti Hartert Alauda arvensis herberti Hartert, 1923d: 149 (Bangkok, Siam). Now Alauda gulgula herberti Hartert, 1923. See Peters, 1960a: 70, Robson, 2000: 476, and Dickinson et al., 2001a: 93. LECTOTYPE: AMNH 555589, adult male, collected in Bangkok, 13°44′N, 100°30′E (Times Atlas), Thailand, on 31 March 1915, by W.J.F. Williamson. From the Rothschild Collection. COMMENTS: In the original description, Hartert (1923d: 149) said that the type, an adult male collected by Williamson on 31 March 1915, was in the Rothschild Museum; in his list of Rothschild types, he (Hartert, 1928: 210) did not add any further information. There are two adult males collected on 31 March 1915, which would therefore have to be considered syntypes. The above specimen, AMNH 555589, bears the Rothschild type label and the Rothschild Collection label marked ‘‘Type of Alauda arvensis herberti Hartert’’ in Hartert’s hand. It is undoubtedly the specimen intended as the type and I hereby designate it the lectotype to ... : Published as part of LeCROY, M. A. R. Y., 2003, TYPE SPECIMENS OF BIRDS IN THE AMERICAN MUSEUM OF NATURAL HISTORY. PART 5. PASSERIFORMES: ALAUDIDAE, HIRUNDINIDAE, MOTACILLIDAE, CAMPEPHAGIDAE, PYCNONOTIDAE, IRENIDAE, LANIIDAE, VANGIDAE, BOMBYCILLIDAE, DULIDAE, CINCLIDAE, TROGLODYTIDAE, AND MIMIDAE, pp. 1-156 in Bulletin of the American Museum of Natural History 278 (278) on page 28, DOI: 10.1206/0003-0090(2003)278<0001:tsobit>2.0.co;2, http://zenodo.org/record/13256611 ...